The Book of the Pomegranate: Moses de Leons Sefer H-Rimmon - Wolfson, Elliot R. (Brown Judaic Studies, 2020)
The Book of the Pomegranate is a Hebrew edition of an important work by the Spanish kabbalist Moses de Leon (ca. 1240-1305). Sefer Ha-Rimmon, which was written in 1287, is particularly significant for study of the Zohar and the development of a theory of the commandment (mitzvot) and why one should do them.